Identification of the G protein‐coupled estrogen receptor (GPER) in human prostate: expression site of the estrogen receptor in the benign and neoplastic gland. (29th December 2015) - Rago, V.; Romeo, F.; Giordano, F.; Ferraro, A.; Carpino, A.
Summary: Estrogens are involved in growth, differentiation and pathogenesis of human prostate through the mediation of the classical estrogen receptors ERα and ERβ. The G protein‐coupled estrogen receptor (GPER) is a 'novel' mediator of estrogen signaling which has been recently recognized in some human reproductive tissues, but its expression in the prostate gland is still unknown. Here, we investigated GPER in benign (from 5 patients) and neoplastic prostatic tissues (from 50 patients) by immunohistochemical analysis and Western blotting. Normal areas of benign prostates revealed a strong GPER immunoreactivity in the basal epithelial cells while luminal epithelial cells were unreactive and stromal cells were weakly immunostained. GPER was also immunolocalized in adenocarcinoma samples but the immunoreactivity of tumoral areas decreased from Gleason pattern 2 to Gleason pattern 4. Furthermore, a strong GPER immunostaining was also revealed in cells of pre‐neoplastic lesions (high‐grade prostatic intra‐epithelial neoplasia). Western blot analysis of benign and tumor protein extracts showed the presence of a ~42 kDa band, consistent with the GPER molecular weight. An increase in both pAkt and p cAMP‐response‐binding protein (pCREB) levels was also observed in poorly differentiated PCa samples. Finally, this work identified GPER in the epithelial basal cells of benign human prostate, with a different localization with respect to the classical estrogen receptors. Furthermore, the expression of GPER in prostatic adenocarcinoma cells was also observed but with a modulation of the immunoreactivity according to tumor cell arrangements.